Biology of Spirama retorta (Lepidoptera: Noctuidae), a new pest of Acacia mangium in Peninsular Malaysia - Sajap, Ahmad Said; Abd. Wahab, Yaacob; Marsidi, Aidah (Forest Research Institute Malaysia, 1997)
An outbreak of Spirama retorta (Lepidoptera: Noctuidae), affecting 800 ha of a one-year-old Acacia mangium plantation, occurred in May to October 1992 in Gunung Besaut Forest Reserve, Perak, Peninsular Malaysia. In the laboratory, more than 60% of larvae reared on A. mangium leaves reached adult stage. Development from egg to adult took 42 days through seven instars requiring 27 days. The moth was medium - sized, having red abdomen and an eyespot on its forewing. The female (x̄ = 64.4 mm), bigger than the male, had greyish-orange forewings with prominent eyespots. The male(x̄ = 58.8 mm) had dark brown to almost black forewings with less conspicuous eyespots. The life table parameters recorded from laboratory population were: the net reproductive rate (Ro) of 203.2, the mean generation time (Tc) of 43.3 days, the intrinsic rate of increase (r m) of 0.1 and the doubling time of 5.6 days. Results from biweekly sampling showed that the infestation, indicated by the number of trees with larvae, varied from 30% at the beginning of the study, rose to more than 60% in the fourth week and dropped to less than 10% at the end of the fourteenth week. Three tachinids, Carcelia sp., Exorista sp. and Blepharella sp., emerged from field collected larvae. Larval-pupal mortality due to parasitism was 5.6 - 43.3%. Predators, Sycanus leucomesus (Reduviidae), Cantheconidea furcellata (Pentatomidae), Mallada basalis (Chrysopidae) and Vespa affinis indosinensis (Vespidae) were observed feeding on the larvae.